Differential synergy of Notch and T cell receptor signaling determines αβ versus γδ lineage fate - Garbe, Annette I. (The Rockefeller University Press, 2006)
Thymic precursors expressing the pre–T cell receptor (TCR), the γδTCR, or the αβTCR can all enter the CD4(+)8(+) αβ lineage, albeit with different efficacy. Here it is shown that proliferation and differentiation of precursors with the different TCRs into αβ lineage cells require Notch signaling at the DN3 stage of thymic development. At the DN4 stage, Notch signaling still significantly contributes to the generation of αβ T cells. In particular, in αβ lineage commitment, the pre-TCR synergizes more efficiently with Notch signals than the other two TCRs, whereas γδTCR-expressing cells can survive and expand in the absence of Notch signals, even though Notch signaling enhances their proliferation. These observations suggest a new model of αβ versus γδ lineage choice in which lineage fate is determined by the extent of synergy between TCR and Notch signaling and in which the evolutionarily recent advent of the cell-autonomously signaling pre-TCR increased the efficacy of αβ T cell generation.